Donor Care - Güvenç Doğan; Oğuzhan Kayhan; Selçuk Kayır; Oktay Demirkıran (Galenos Yayinevi, 2023)
Donor care consists of the treatments applied to patients diagnosed with brain death in the intensive care unit. After the diagnosis of brain death and during the procedures of organ donation, appropriate donor care with a multidisciplinary approach is critical in increasing the success of transplantation.With donor care, hemodynamic, hormonal and inflammatory disorders caused by brain death should be prevented or corrected. The main purposes should be minimizing donor loss during the care, healing of initially medically unsuitable organs, increasing the number of organs retrieved and increasing the number of the good results.